1971
DOI: 10.1246/bcsj.44.2296
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Effects of the Reactant in the Liquid-phase Isomerization of m-Xylene over a Silica-Alumina Catalyst under Pressure

Abstract: The activity of silica-alumina catalyst in the isomerization of m-xylene was measured at the temperatures of 290°C, 320°C, 380°C, and 430°C in the liquid phase under a pressure of 300 kg/cm2. The observed activities were considerably higher than those in vapor-phase reactions, moreover even after 20 days practically no decline in the activity was observed except for the measurements at 430°C. This superior ability of the catalyst in the liquid phase can be ascribed to the cleaning effect of the liquid reactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Takaya et al have shown that catalyst deactivation can be avoided by carrying out the reaction in the liquid phase. 37 Thus, the activity of an ASA sample was found to be stable for prolonged reaction time. The increased stability was explained by the solvation of diphenylmethanes by liquid m-xylene.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Takaya et al have shown that catalyst deactivation can be avoided by carrying out the reaction in the liquid phase. 37 Thus, the activity of an ASA sample was found to be stable for prolonged reaction time. The increased stability was explained by the solvation of diphenylmethanes by liquid m-xylene.…”
Section: Resultsmentioning
confidence: 95%
“…Further condensation of the heavy intermediates causes coke to deposit, which leads to irreversible deactivation. Takaya et al have shown that catalyst deactivation can be avoided by carrying out the reaction in the liquid phase . Thus, the activity of an ASA sample was found to be stable for prolonged reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst coking in xylenes isomerization has been studied in detail by Takaya et al (1971Takaya et al ( , 1972a, who observed an abundance of trimethyl and tetramethyl diphenylmethanes in the coking products. If we assume that two adjacent adsorbed xylene molecules are involved in the formation of a coke precursor P, ultimately leading to coke lay-down according to the scheme AX + AX --P + Xcoke + X slow then a balance on active sites leads to the relation…”
Section: Product Distribution and Reaction Networkmentioning
confidence: 99%
“…20 Additionally, the liquid phase conditions allowed continuous removal of products from the catalyst bed, thus reducing carbonaceous deposits. 21 While zeolite HY was also applicable for the aromatization of larger alkyl methyl ketones, such as 2-butanone and 2-pentanone, its overall activity was still lacking regarding a potential process development for future integration into a biorefinery. 19 In the course of the catalyst development, combining high activity with long-term operational stability remains an ongoing problem that we sought to solve by using large pore amorphous aluminosilicates as acid catalysts.…”
Section: Introductionmentioning
confidence: 99%